2023
DOI: 10.1002/cche.10706
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning technique unraveled subspecies‐specific ionomic variation with the preferential mineral enrichment in rice

Abstract: Background and ObjectivesTo enrich micronutrients in rice through breeding, screening a large diversity panel of major sub‐species of rice accessions for their ionomes is necessary.FindingsInductively coupled plasma optical emission spectroscopy (ICP‐OES) was deployed to profile grain ionomes from 1100 rice accessions. Classification models derived for multi‐dimensional ionomics data using random forest model, support vector machine, and artificial neural network predicted three distinct groups differ in ionom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…However, our results align with Jiang et al. (2007) and Tiozon et al. (2023) , who reported a significantly negative correlation between amylose content and K, Mg, and Mn levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our results align with Jiang et al. (2007) and Tiozon et al. (2023) , who reported a significantly negative correlation between amylose content and K, Mg, and Mn levels.…”
Section: Discussionsupporting
confidence: 91%
“…Although rice is not known to be mineral-rich, it can still serve as an essential source of caloric energy and macro-micro nutrients for those who consume it as a staple food ( Huang et al., 2020 ). Except for genotypic influences, environmental factors have been documented to affect minerals in rice grain ( Du et al., 2013 ; Huang et al., 2016 ; Tiozon et al., 2023 ). Previous studies have shown that atmospheric CO 2 levels and temperature ( Myers et al., 2014 ; Chaturvedi et al., 2017 ), application of nitrogen ( Gu et al., 2015 ; Wang et al., 2018 ) and water management ( Xu et al., 2019 ) could affect the mineral nutrients of rice grains.…”
Section: Discussionmentioning
confidence: 99%